Neutrino observations of LHAASO sources: Present constraints and future prospects. Issue 1 (8th June 2022) - Huang, Tian-Qi; Li, Zhuo
ABSTRACT: The Large High Altitude Air Shower Observatory (LHAASO) observed a dozen gamma-ray sources with significant emission above 100 TeV that may be strong candidates for PeVatrons. Neutrino observations are crucial for diagnosing whether the gamma-ray radiative process is hadronic or leptonic. We use the Bayesian method to analyse the 10-yr (2008–2018) IceCube data, and hence constrain the hadronic gamma-ray emission in the LHAASO sources. The present neutrino data show that the hadronic gamma-ray flux from the Crab Nebula is lower than the observed gamma-ray flux at the 90 per cent confidence level and contributes less than 86 per cent, which disfavours the hadronic origin of gamma-rays below tens of TeV. For the other LHAASO sources, the present neutrino observations cannot put useful constraints on the gamma-ray radiative process. We consider the uncertainty of the source extension: the upper limits on the hadronic gamma-ray flux tend to increase with the extension; and some sources, namely LHAASO J2032+4102, LHAASO J1929+1745, and LHAASO J1908+0621, show a relatively high statistical significance of neutrino signals if the extension is ≲ 0.°6. Finally, we estimate the future observational results of LHAASO sources by proposed neutrino telescopes. If the LHAASO-observed PeV gamma-rays are of hadronic origin, the Crab Nebula may be detected at >100 TeV at the 3σ confidence level within 20 years by a neutrino detector with an effective area 30 times that of IceCube.